2019
DOI: 10.1002/masy.201700079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aging Resistance in UHMWPE/LLDPE Blend‐Based Carbon Nanotubes Nanocomposites

Abstract: Ultra high molecular weight polyethylene (UHMWPE)/linear low density polyethylene (LLDPE) blend‐based carbon nanotubes nanocomposites with different contents of LLDPE are prepared using a high speed homogenizer. Samples of the materials are thermally treated to understand the correlation between the degree of crystallinity of the treated samples and their impact resistance. Promising results are obtained for the nanocomposite with 10 wt% of LLDPE that shows similar behavior to neat UHMWPE, with the advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…According to the Tukey's test, both samples are statistically different, displaying a reduction of about 12% in the impact resistance value. This reduction was expected since the addition of CNTs increases the stiffness of the polymer matrix and consequently reduces the impact strength, and similar results were found in the literature [37]. Moreover, PHBV/CNT nanocomposite suffered a reduction in the impact strength because the dispersion of CNTs into PHBV matrix was not good enough, changing the tenacity mechanism and consequently reducing the energy absorption [38,39].…”
Section: Notched Izod Impact Strengthsupporting
confidence: 82%
“…According to the Tukey's test, both samples are statistically different, displaying a reduction of about 12% in the impact resistance value. This reduction was expected since the addition of CNTs increases the stiffness of the polymer matrix and consequently reduces the impact strength, and similar results were found in the literature [37]. Moreover, PHBV/CNT nanocomposite suffered a reduction in the impact strength because the dispersion of CNTs into PHBV matrix was not good enough, changing the tenacity mechanism and consequently reducing the energy absorption [38,39].…”
Section: Notched Izod Impact Strengthsupporting
confidence: 82%
“…Table 2 also shows a decrease in the degree of crystallinity with the addition and increase of CNT concentration. Although CNT acts as a nucleating agent, when homogeneously dispersed in polymeric matrices and higher concentrations, they can act as a physical barrier, due to their length, for the growth of crystallites, hindering the crystallization of the polymer [17,81]. The PHBV/CNT nanocomposite has a higher degree of crystallinity than PHBV/CNT-rec, which may be related to the better distribution of CNT in the matrix and the more real content of CNT in the final material.…”
Section: Characterization Of Nanocomposites Films 321 Differential Sc...mentioning
confidence: 99%
“…Fouad et al, 21 has investigated the HDPE/CNT nanocomposites prepared via extrusion blending technique and the findings reported that 4 wt% of carbon nanoparticles to improve storage and Young's modulus and yield strength without affect the melting temperature. Da Silva and co‐authors 22 reported that inclusion of 0.5 wt% loading of CNT had reduced the water absorption capacity of ultra‐high molecular weight polyethylene (UHMWPE)/linear low‐density PE blends. Similar reduction in water absorption results with the incorporation of 5% CNT in HDPE composites due to the ease of its crystallization 19 …”
Section: Introductionmentioning
confidence: 99%